AQU-019 exhibits protective effect on bacterial infection induced gastroenteritis in rat model. (January 2022) - Sun, Qian; Liu, Yuhua; Zhang, Jingjing; Li, Yuanfei
Abstract: Gastroenteritis is a commonly diagnosed disease which sometimes may lead to hospitalization of the patients due to complications such as sepsis and dehydration. In the present study protective effect of AQU-019 against Salmonella enterica ( S.enterica ) induced gastroenteritis in rat model was investigated. Treatment of S.enterica infected rats with AQU-019 prevented intestinal tissue damage effectively in dose-dependent manner. The characteristic pathological features induced by S.enterica infection in rat intestines included, edema development, submucosal infiltration of leukocytes and cell necrosis. AQU-019 treatment at 1.25, 2.5, 5 and 10 mg/kg doses led to a significant ( p  < 0.05) reduction in MPO activity in the intestinal tissues of S.enterica infected rats. AQU-019 treatment effectively reversed S.enterica infection mediated reduction in ZO-1 and occludin expression in rat intestines. Urine volume of the AQU-019 treated rats increased significantly ( p  < 0.05) from day 2 to day 7 compared to the S.enterica infected group. Urine pH didn't showed any change in S.enterica infected rats on treatment with AQU-019 on day 1 to day 7. The bacterial numbers showed a significant ( p  < 0.05) decrease in S.enterica infected rat feces, urinary bladder and urethra on treatment with AQU-019. In summary, AQU-019 prevents intestinal epithelial damage and inhibits infiltration of neutrophils in S.enterica infected rats. Tight junction related protein expression was also regulated in S.enterica infected rats by AQU-019 treatment. Therefore, AQU-019 may be developed as a potent candidate for treatment of bacterial infection induced gastroenteritis. Highlights: Treatment of S.enterica infected rats with AQU-019 prevented intestinal tissue damage. AQU-019 treatment led to a significant ( p  < 0.05) reduction in MPO activity in the intestinal tissues of S.enterica infected rats. AQU-019 treatment effectively reversed S.enterica infection mediated reduction in ZO-1 and occludin expression in rat intestines. Urine volume of the AQU-019 treated rats increased significantly ( p  < 0.05) from day 2 to day 7 compared to the S.enterica infected group. The bacterial numbers showed a significant ( p  < 0.05) decrease in S.enterica infected rat feces, urinary bladder and urethra on treatment with AQU-019.